Cut-off Value of 50-g Glucose Challenge Test for The Diagnosis of Gestational Diabetes Mellitus - Dittakarn Boriboonhirunsarn; Tripop Lertbunnaphong; Pawantee Khanmali (The Royal Thai College of Obstetricians and Gynaecologists, 2013)
Objective: To determine the cut-off value of 50-g glucose challenge test (GCT) for the diagnosis of gestational diabetes mellitus (GDM) among Thai pregnant women.Materials and Methods: A study was conducted at the Department of Obstetrics and Gynecology, Faculty of Medicine Siriraj Hospital. Data of 816 pregnant women who were at risk for GDM with abnormal 50-g GCT results (≥140 mg/dL) before 20 weeks of gestation were included. All women received 100-g oral glucose tolerance test (OGTT) for GDM diagnosis. This approach was repeated during 24-28 weeks of gestation among those with normal 100-g OGTT results. Medical records were reviewed for data collection. Positive predictive values for GDM diagnosis were estimated at different cut-off levels of 50-g GCT, using 10 mg/dL increment interval.Results: Mean age was 32.4±5.1 years, and mean gestational age when 50-g GCT was initially performed was 10.1±5.9 weeks of gestation. GDM was diagnosed in 290 cases (35.5%) and mean gestational age at diagnosis was 19.1±10.3 weeks. The positive predictive values for GDM diagnosis increased with 50-g GCT values. Of 19 and 13 women whose 50-g GCT values were ≥230 and ≥240 mg/dL, 90.5% and 100% were diagnosed with GDM, respectively. Conclusion: 50-g GCT before 20 weeks of gestation could be applied and used for diagnosis of GDM using appropriate cut-off value.